SUNAN GESENG AND HIS PREACHING LEGACY IN CENTRAL JAVA AND YOGYAKARTA - Nurfaizah, Halimah; Suranta, Suranta (UI Scholars Hub, 2023)
Traditional histories are manifestations of Indonesia's cultural richness. These traditional histories encompass the legend of influential figures in the spread of Islam in Central Java and The Special Region of Yogyakarta, such as Sunan Geseng. This article will discuss about the history of Sunan Geseng based on stories from the local communities in the preaching areas of Sunan Geseng and the traces of him. The research is considered as qualitative research using the method of library studies and interview. The theory used in this study is the theory of folklore, especially religious legends. The result of this research tells that Sunan Geseng is a student of Sunan Kalijaga, who is originated from Purworejo, Central Java. He was given a nickname